The Pentagon's Brain : an uncensored history of DARPA, America's top secret military research agency - Jacobsen, Annie (New York: Back Bay Books, Little, Brown and Company, 2024)
Since its inception in 1958, the Defense Advanced Research Projects Agency, or DARPA, has grown to become the Defense Department's most secret, most powerful, and most controversial military science research and development agency. Created by President Eisenhower to prevent another Sputnik, and to focus primarily on defensive programs against nuclear weapons, the agency--and its imagination and scope--has expanded enormously with each passing year. From Agent Orange in Vietnam to insect-sized drones in use today, from the earliest networked computers and the Internet to smart rockets and war zones under 24-hour video surveillance, DARPA is responsible for innovations that have changed the course of war, national security, and strategic planning at the highest levels. To uncover the secret history of DARPA in action, journalist Annie Jacobsen tracked down key players in DARPA's Smart Weapons Program, past and present; neuroscientists building an artificial brain, cell biologists working on limb regeneration, the Nobel laureate who invented the laser. From DARPA's earliest defensive advances to hundreds of ongoing programs, Jacobsen exposes both sides of the DARPA coin: the fantastic technological advances from which we all benefit, and the darker side drawn up in a race for military supremacy. Based on information from inside sources, exclusive interviews, private documents, and declassified memos, The Pentagon's Brain reads like science fiction but is absolutely true, a groundbreaking look behind the scenes at the clandestine intersection of science and the American military.--Publisher information.
Keywords: Science and State -- United States; Technology and State -- United States; Military Research